Police Perceptions of Computer Crimes in Two Southeastern Cities: An Examination from the Viewpoint of Patrol Officers - Holt, Thomas J. (American journal of criminal justice, 2012)
Although scholars and law enforcement administrators have provided input on how local law enforcement is responding to various forms of computer crime and how officers perceive of it, patrol officers have been rarely surveyed to understand their perceptions of computer crime. Examining officer perceptions is vital considering that patrol officers are being asked to be more effective first responders to digital forensic crime scenes as a critical step in combating computer crimes at the local level. This study therefore addressed this gap by surveying patrol officers in two southeastern cities regarding their perceptions of computer crime, specifically regarding its uniqueness, offenders and targets, and seriousness and frequency in comparison to traditional forms of crime. Results indicated that many officers do not have strong opinions on several aspects of computer crime. However, they perceive it to be a serious problem and consider some computer crimes to be as serious as traditional forms of crime.